2011
DOI: 10.1080/08959420.2011.579503
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Late-Life Mental Disorders in Primary Care: We Can Do a Better Job

Abstract: Health care services provided to older adults today are not as effective as they should be. The quality of care for late-life mental disorders often falls short of desired standards. The growth of the elderly population makes it imperative for the health care system to address late-life mental disorders more effectively. Intervention strategies based in primary care settings show the most promise, but effectiveness will depend on solving the geriatric psychiatry workforce crisis. Collaborative care is one prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Research also showed that primary care providers can play a significant role in MHCE . Most of the elderly regularly meet their General practitioner (GP), which implies that these professionals are well‐positioned to address MHP in their older patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research also showed that primary care providers can play a significant role in MHCE . Most of the elderly regularly meet their General practitioner (GP), which implies that these professionals are well‐positioned to address MHP in their older patients.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the elderly regularly meet their General practitioner (GP), which implies that these professionals are well‐positioned to address MHP in their older patients. Moreover, the elderly population prefers receiving their (mental) healthcare in primary care settings instead of in specialised mental healthcare institutions . Some studies, however, show that a lack of knowledge, skills, and confidence in GPs regarding MHCE could substantially impair detection as well as treatment of MHP in the elderly …”
Section: Resultsmentioning
confidence: 99%
“…Mental health professionals are expensive and rarely integrated into primary care practices (Moak, 2011). A growing literature finds that expert and nonexpert providers produce comparable results in treating anxiety and depression (den Boer et al, 2005; Montgomery et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to improve the awareness about mental disorders in late-life both at the community level and among health professionals and epidemiologic studies demonstrating the improvement of appropriate health care for the elderly with mental illness will open the way to Collaborative care, one promising model for improving geriatric mental health care delivery in primary care. Public policy should reflect the essential role of psychiatry in geriatrics and promote the integration of geriatric psychiatry with primary care [22].…”
Section: Discussionmentioning
confidence: 99%
“…Two or more disorders occurred in 11.6% of participants and three or more in the 5.3% [21]. Since services dedicated to older psychiatric patients have claimed to be not fully effective [22] and improvements are needed in the screening and prevention of 'Common Mental Health Disorders' [23] more research is needed to provide informative figures of mental disorders occurrence in late-life.…”
Section: Introductionmentioning
confidence: 99%